Please solve it ....


4 .     f ( x )     =   2 x 2   -   x   +   1   -   1 x   +   1   -   2 x   -   1 x 3   +   1

Dear Student,

Since your question is unclear, I am assuming that we are required to find the derivative of fx:Let fx = y = 2x2 - x + 1 - 1x + 1 - 2x - 1x3 + 1= 2x + 1 - x2 - x + 1x2 - x + 1x + 1 - 2x - 1x3 + 1= 2x + 2 - x2 + x - 1 - 2x + 1x3 + 1= 2 + x - x2x3 + 1 = yTaking logs on both sides,log y = log 2 + x - x2x3 + 1 log y = log 2 + x - x2x3 + 112 log y = 12 log 2 + x - x2x3 + 1                                         log ab = b log a log y = 12 log 2 + x - x2 - log x3 + 1             log ab = log a - log bDifferentiating both sides with respect to x,1ydydx = 1212 + x - x21 - 2x - 1x3 + 13x2 dydx = y21 - 2x2 + x - x2 - 3x2x3 + 1, where y =2x2 - x + 1 - 1x + 1 - 2x - 1x3 + 1 

​Hope this information will clear your doubts about topic.

If you have any more doubts, please ask here on the forum and our experts will try and help you out as soon as possible.

Regards

  • 0
What are you looking for?